Impact of SWCC Measurement Methods on the Numerical Investigations of Unsaturated Soils - Mihoubi, Abderrahim; Benmoussa, Samir; Houam, Abdelkader; Laouar, Mohamed Salah (Journal of Applied Engineering and Technological Science (JAETS), 2025)
The soil-water characteristic curve SWCC, also known as the soil-water retention curve SWRC, describes the relationship between soil suction and water content in unsaturated soils. Many studies rely on specific laboratory testing methods without considering their impact on numerical simulations. This research investigates the effect of different SWCC measurement techniques on numerical modeling outcomes. Soil samples from the Tebessa region were tested using three methods: the filter paper method, the osmotic technique, and the axis translation technique. Numerical simulations were then conducted using FLAC software to analyze the influence of these methods on the hydromechanical properties of unsaturated soils and slope stability under two days of wetting conditions. The results indicate that the selected SWCC measurement method significantly affects the predicted vertical suction profile and influence the factor of safety (FOS) in slope stability analysis. This suggests that while accurate suction measurements are crucial for understanding soil behavior, their overall impact on slope stability predictions varies depending on the testing technique employed.